SISTEM PEMESANAN KAMAR HOTEL DENGAN BOOTSTRAP MENGGUNAKAN METODE UCD PADA SIMALUNGUN CITY HOTEL - Gabriel Febriady Simbolon; Romer Airyanto Sinaga; M. Bobbi Kurniawan. Nasution; Farida Gultom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Manual hotel room reservations are still common by local hotels such as Simalungun City Hotel. This process poses various problems, such as time inefficiency, the risk of recording errors, and limited access to information for customers. This research aims to design and develop a web-based hotel room booking system with a User-Centered Design (UCD) approach and the utilization of the Bootstrap framework, which aims to improve ease of access, service efficiency, and user experience. The UCD approach ensures the system is designed based on the needs and characteristics of the user through an iterative process from analysis to evaluation. The use of Bootstrap supports a responsive and consistent interface on a wide range of devices. The system includes room search, booking, confirmation, and data management features by admins. The results of the implementation show that this system is able to improve data accuracy, service speed, and user satisfaction. Thus, this system supports the digital transformation of Simalungun City Hotel significantly.